2019
DOI: 10.1109/access.2019.2938874
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency Optimization for Secure Transmission in MISO Cognitive Radio Network With Energy Harvesting

Abstract: In this paper, we investigate different secrecy energy efficiency (SEE) optimization problems in a multiple-input single-output underlay cognitive radio (CR) network in the presence of an energy harvesting receiver. In particular, these energy efficient designs are developed with different assumptions of channels state information (CSI) at the transmitter, namely perfect CSI, statistical CSI and imperfect CSI with bounded channel uncertainties. In particular, the overarching objective here is to design a beamf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 78 publications
(121 reference statements)
0
19
0
Order By: Relevance
“…Nowadays, the exponential growth of data traffic and mobile computing have brought the increasing demands for wireless communication, such as scarce spectrum resources and energy supply [1]. As a promising approach to simultaneously improving both spectrum efficiency (SE) and energy efficiency (EE) in fifth generation (5G) and beyond wireless networks, the energy harvesting (EH) cognitive radio network (CRN) has recently attracted great research attention [2]. In contrast to other natural-resource EH techniques (such as solar, wind and thermal), the radio frequency (RF)-based EH technology is more suitable for stable energy provision [3].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the exponential growth of data traffic and mobile computing have brought the increasing demands for wireless communication, such as scarce spectrum resources and energy supply [1]. As a promising approach to simultaneously improving both spectrum efficiency (SE) and energy efficiency (EE) in fifth generation (5G) and beyond wireless networks, the energy harvesting (EH) cognitive radio network (CRN) has recently attracted great research attention [2]. In contrast to other natural-resource EH techniques (such as solar, wind and thermal), the radio frequency (RF)-based EH technology is more suitable for stable energy provision [3].…”
Section: Introductionmentioning
confidence: 99%
“…To exploit different potential benefits, NOMA has been recently integrated with different technologies such as cognitive radio (CR) [13], millimeter-wave [14] [15], multiple-antenna techniques [16], [17], [18] and conventional OMA techniques [19]. In particular, the combination of NOMA with spatial domain multiple access (SDMA) offered by multipleantenna can provide additional benefits, by jointly utilizing both the spatial and power domains.…”
Section: Introductionmentioning
confidence: 99%
“…In [ 22 ], the system goal was to maximize secrecy EE by jointly optimizing the confidential signal’s power, the artificial noise power, and the power-splitting ratio. In [ 23 ], the goal was to design a beamforming technique maximizing the secrecy EE, where an efficient iterative algorithm was presented.…”
Section: Introductionmentioning
confidence: 99%
“… Although some existing works investigated the EE for DAS with RF EH, only the constraint of power control was considered, where the user’s information rate requirement was not involved; see, e.g., [ 17 , 18 ], while in our work, the system EE is maximized with the user’s minimal information rate requirement, which is much closer to the users’ demands. Different from the most similar existing works [ 22 , 23 ] where the linear EH model was used, in this work, the nonlinear EH model is adopted, as it was reported that the nonlinear EH one was obtained with real measurement data [ 26 , 27 ]. Thereby, our work may be much closer to the practical situation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation